Foreign Body Aspiration: The Journey of needle in Left Bronchus : A Case Report - Cut Asmaul Husna; Teuku Zulfikar; Nina Herlina (Proceedings of Malikussaleh International Conference on Health and Disaster Medicine (MICOHEDMED), 2024)
Foreign body aspiration is a challenge that requires rapid and accurate diagnosis. It can lead to partial and complete airway obstruction and potentially life-threatening event. We present the case of a 12-years-old female who inhaled the pin (needle) since ± 2 weeks ago. The needle position  falls in a sharp upward. The patient had cough for ± 30 minutes after the accident, and complained feeling of lump in the middle of the chest 1 week after the accident, especially when the patient’s breathe. No painful swallowing, history of choking, and vomiting mixed with blood. The physical examination and laboratory were normal limits. Chest X-ray shows the foreign body in the trachea with a vertical position at the level of 3-5 thoracic vertebrae. The flexible bronchoscopy was performed and showed left lower lobe was hyperemic and the corpus alienum appeared which was then successfully evacuated. The patient was treated with antibiotics and anti-inflammatory drugs. The patient was stable and discharge. In this case the needle entered the left lower lobe bronchus, so it took a challenge in the evacuation process. Flexible bronchoscopyc removal is the mainstay of management of foreign body in tracheobronchial tree.